The Ionospheric Refractivity Effects on the GPS Signals - Ünver, Onur; Guyer, Sinan; Uzel, Turgut; Can, Zehra (IEEE, 345 E 47Th St, New York, Ny 10017 Usa, 2013)
The communication between the global navigation satellites and ground observation stations is provided by the electromagnetic waves that emits from the satellites. When the satellite signals pass through the Ionosphere, they are refracted by the different Ionospheric layers. The precise determination of the Ionospheric refractivity index is crucial for the evaluation of the Ionospheric delay that depends on the refraction ratio. The electromagnetic waves that passes through the Magnetoionic medium interacts with the medium depending upon the free electron content and plasma frequency. As a consequence of that interaction the medium shows the dispersive and refractive effects on the waves. The phase and group velocity of an electromagnetic wave in the vacuum are equal and advances with the speed of light, on the other hand in the plasma medium there is a relativistic difference between the phase and group velocities, and this difference depends on the refractivity index of the medium. The refractivity shows varieties depending upon the free electron content of the medium, external magnetic field, gyrofrequency of electrons and plasma frequency. In the earth's atmosphere the layer that locates the altitude 501000 km and contains free electrons and positive ions as a result of the effects of the solar radiation and solar energetic particles is called as Ionosphere. In the Ionosphere, the thermal effects on the electrons are low level so this region is termed "cold plasma". In the Ionospheric researches, due to mass of the positive ions higher than mass of the electrons, ion motions are neglected. In terms of quality and quantity, Ionosphere shows the Magnetoionic medium effects on the electromagnetic waves. In this study, the variations of the Ionospheric refractivity index on the GPS signals due to different Ionospheric conditions is examined and made a comparison with the results of the literature.
Keywords: Ionosphere; Refractivity index; GPS Signals